Casa das mangueiras: espaço de aprendência no cotidiano de adolescentes com vivência de rua. - Lopes, Osvaldo Tadeu (2004)
This research work is a study of case undertaken at Escola Experimental Casa das Mangueiras, a non-governmental organization created in the 70 s and which showed to be the pioneer in the development of a pedagogic experience with teenagers of age ranging between 12 to 17 years old, who committed infractions to Law. The target of this research was to try to understand the logic which moves and gives life to the educational action of the teachers belonging to this institution, as well as, how comes out the process of re-organizing their lives (boys and girls), who experienced that situation. The empirical data was built from a spring of the researcher in the daily life of the institution, the notes made every day in a field diary; interviews were undertaken with the founders of this non-governmental organization aiming at rescuing the history of the institution and also rescuing aspects of their lives. Besides two interviews were made with a boy and a girl who re-organized their lives, leaving criminality behind. The constructed data with the subjects of research were analyzed from the Giznburg s indicatory paradigm, i.e., listening to deaf clues and putting attention to not uttered speech; Assmann s concept of learning, which does not separate cognitive process from those vital ones; Balandier and Morin, using the concept of order/disorder and the work with uncertainties; among others to cite some. The results indicated that the spirituality is an important element which gives direction to the work developed by the educators and that the pedagogic experience developed at the non-governmental organization is new and innovative due to the immersion of the educators in the daily life of the teenagers who lived in the street, by incorporating the disorder in the educators work, opening to reality and the uncertainties that life brings.